A Study On Motives In Knowledge Sharing Portals Via Online Collaboration - Sabetzadeh, Farzad (2008)
This study tries to give a wider scope hand in hand with all phases of knowledge cycle to clarify concept of online collaboration which is the fruit of synergy of all stages of knowledge cycle and is reinforced when there is a satisfactory synchrony among different components.